1994
DOI: 10.1128/jb.176.15.4742-4749.1994
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Bacillus thuringiensis HknA, a histidine protein kinase homology, bypasses early Spo mutations that result in CryIIIA overproduction

Abstract: The Bacillus thuringiensis CryIIIA insecticidal crystal protein (ICP) is a vegetatively expressed protein that is toxic to coleopteran insect larvae. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis of the asporogenous B. thuringiensis subsp. morrisoni strain EG1351, which harbors the native cryIIIA-encoding 88-MDa plasmid, showed a 2.5-fold overproduction of the CryIIIA protein compared with that of an isogenic wild-type strain. Further studies showed that neither CryIIIA protein synthesis n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…Class 4 HK 39 clustered closest to HKs of non-spore-forming bacteria, such as AtoS of Escherichia coli. However, overexpression of a HK 39 orthologue in B. thuringiensis EG1351 has been shown to bypass sporulation defects and a spo0F mutation in different B. thuringiensis strains (Malvar et al, 1994). In addition, it has recently been shown that HKs 39, 40, 48 (KinD orthologue), 49 (KinB orthologue) and 50 are capable of inducing sporulation in B. anthracis (Brunsing et al, 2005).…”
Section: Matching Of 'Orphans'mentioning
confidence: 99%
“…Class 4 HK 39 clustered closest to HKs of non-spore-forming bacteria, such as AtoS of Escherichia coli. However, overexpression of a HK 39 orthologue in B. thuringiensis EG1351 has been shown to bypass sporulation defects and a spo0F mutation in different B. thuringiensis strains (Malvar et al, 1994). In addition, it has recently been shown that HKs 39, 40, 48 (KinD orthologue), 49 (KinB orthologue) and 50 are capable of inducing sporulation in B. anthracis (Brunsing et al, 2005).…”
Section: Matching Of 'Orphans'mentioning
confidence: 99%
“…Another E E -driven operon, the glycogen operon, which is repressed by glucose in sporulating cells of B. subtilis, also supports the need for metabolic control of the stationary-phase phenomenon (19). In the light of the remarkable conservation of sigma subunits between B. thuringiensis and B. subtilis, the temporal regulation of sporulation in B. thuringiensis through the cascade of sigma factors is believed to be closely similar to that of B. subtilis (1,21,23,24). Homologs of several important transcription factors described in B. subtilis have been identified in B. thuringiensis also (1).…”
Section: Discussionmentioning
confidence: 81%
“…Our previous studies have shown that CryIIIA protein production is increased 2.5-fold in the asporogenous B. thuringiensis strain EG1351 (9). We have suggested that this is a consequence of the sporulation-independent transcription of the cryIIL4 gene (4,12,13), the terminal stationary phase arising from an early Spo-defect in EG1351, and the failure to induce sporulation-specific proteases (9). Additionally, our observations that either multicopy hknA or kinA can bypass the sporulation defect in EG1351 and the spoOF defect in EG1634 have led us to propose that the EG1351 defect occurs in the SpoOA phosphorylation cascade (9).…”
mentioning
confidence: 90%
“…The transposon vector pEG922 (3) containing the recently described class II B. thuringiensis transposon TnS401 (3) was used to construct a transposoninsertion library in B. thuringiensis EG10368 essentially as described by Youngman (16). Subsequent screening of the library on nutrient sporulation medium (NSM) plates identified 25 colonies with a translucent appearance, characteristic of sporulation mutants (9), with sporulation frequencies of less that 104 spores per ml. To identify the B. thuringiensis DNA at each transposition site, chromosomal DNAs prepared from each of the Spo-isolates (7) and oligonucleotide primer TM1 (Integrated DNA Technologies Inc. [ Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation